Associations between physical activity, nutritional status, and gross motor competence among elementary school children in lembah melintang district - Inang Namora Ulfa; Ahmad Chaeroni; Gusril Gusril; Fahd Mukhtarsyaf (SCHOULID: Indonesian Journal of School Counseling, 2026)
The background of this research is that there are still elementary school children in Lembah Melintang District with low levels of physical activity and nutritional status that is not yet normal, which has the potential to affect the development of gross motor skills. Variations in physical activity, nutritional status, and lack of involvement in structured physical activities and active games, coupled with differences in parenting patterns and parental attention, are thought to be related to differences in gross motor skills in children. This study aims to determine the relationship between physical activity and gross motor skills of elementary school children in Lembah Melintang District, to determine the relationship between nutritional status and gross motor skills of elementary school children in Lembah Melintang District, and to determine the relationship between physical activity and nutritional status and gross motor skills of elementary school children in Lembah Melintang District. This study uses a quantitative approach with an associative research type. With a population and sample of 45 students using a total sampling technique. The research variables consist of physical activity, nutritional status, and gross motor skills which are measured using the PAQ-C instrument, anthropometric measurements, and gross motor tests in the form of running and jumping. Data analysis techniques include descriptive analysis, prerequisite tests, and inferential analysis. The results of the study showed that there was a relationship between physical activity and gross motor skills (R 0.404) with a contribution of 16.3%, and nutritional status had a relationship with gross motor skills (R 0.334) with a contribution of 11.2%. There was also a relationship between physical activity and nutritional status with gross motor skills (R 0.519) with a contribution of 26.9%, so it was proven that they complement each other in supporting the gross motor development of elementary school children.